Current knowledge on Mexican tardigrades with a description of Milnesium cassandrae sp. nov. (Eutardigrada: Milnesiidae) and discussion on the taxonomic value of dorsal pseudoplates in the genus Milnesium Doyère, 1840 - Moreno-Talamantes, Antonio; Roszkowska, Milena; García-Aranda, Mario Alberto; Flores-Maldonado, José Juan; Kaczmarek, Łukasz (Zootaxa, 2019)
Mexico is a megadiverse country, however its tardigrade fauna is poorly known and to date 44 species have been reported from this region. In the present paper, an update of the reported Mexican tardigrades is presented, increasing the number of recorded tardigrades to 55 species (11 new records). Moreover, we describe Milnesium cassandrae sp. nov. from State of Nuevo León in northern Mexico. The new species is most similar to Mil. krzysztofi Kaczmarek & Michalczyk, 2007 and Mil. beasleyi Kaczmarek, Jakubowska & Michalczyk, 2012, but it differs from them mainly by details of the dorsal sculpture and some morphometric characters. We also discuss the taxonomic value of a recently described feature, ‘pseudoplates’, for differentiating the taxa within the genus Milnesium Doyère, 1840. [Zoobank URL: urn:lsid:zoobank.org:act:0684AE18-0510-4F7B-B75D-AE5177FBF2A2]